2022
DOI: 10.1186/s13073-022-01110-1
|View full text |Cite
|
Sign up to set email alerts
|

Intratumor heterogeneity and T cell exhaustion in primary CNS lymphoma

Abstract: Background Primary central nervous system lymphoma (PCNSL) is a rare lymphoma of the central nervous system, usually of diffuse large B cell phenotype. Stereotactic biopsy followed by histopathology is the diagnostic standard. However, limited material is available from CNS biopsies, thus impeding an in-depth characterization of PCNSL. Methods We performed flow cytometry, single-cell RNA sequencing, and B cell receptor sequencing of PCNSL cells rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 69 publications
1
9
0
Order By: Relevance
“…Ahn et al suggested that the mean ADC calculated from the whole tumor was the highest performing predictor for distinguishing PCNSL from GBM. Heterogeneity [25][26][27] is mainly possible reason for the inconsistent results of different parameters. And because the cases in this study were atypical GBMs with homogeneous enhancement, the heterogeneity was less pronounced than that of typical GBM, which led to a small difference in the mean ADC obtained from single-section and whole-volume approaches between aGBM and hPCNSL, and the differential diagnostic values were limited; instead, the minimum ADC based on the three-ROIs approach was more meaningful.…”
Section: Discussionmentioning
confidence: 99%
“…Ahn et al suggested that the mean ADC calculated from the whole tumor was the highest performing predictor for distinguishing PCNSL from GBM. Heterogeneity [25][26][27] is mainly possible reason for the inconsistent results of different parameters. And because the cases in this study were atypical GBMs with homogeneous enhancement, the heterogeneity was less pronounced than that of typical GBM, which led to a small difference in the mean ADC obtained from single-section and whole-volume approaches between aGBM and hPCNSL, and the differential diagnostic values were limited; instead, the minimum ADC based on the three-ROIs approach was more meaningful.…”
Section: Discussionmentioning
confidence: 99%
“…By using single-cell RNA sequencing, B-cell receptor sequencing of rare PCNSL cells, and spatial transcriptomics of biopsy samples, results found that malignant B-cell in PCNSL exhibit transcriptional and spatial intratumor heterogeneity. T-cell exhaustion is common in the PCNSL microenvironment, where it co-localizes with malignant cells, highlighting the potential for personalized treatments ( Heming et al, 2022 ). For molecular driver evolution, researchers decipher the intra-tumor and inter-lesion diversity of CTCL patients and propose a multi-step tumor evolution model using single-cell RNA analysis and bulk whole-exome sequencing on 19 skin lesions from 15 CTCL patients.…”
Section: The Application Of Single-cell Omicsmentioning
confidence: 99%
“…A possible explanation of these contradictory findings lies in the fact that the frequency of genetic alterations encompassing PD-1 ligands in PCNSL appears to be much lower than the one initially reported [38 && ,68,69]. In addition, recurrent deletion of HLA genes [38 && ,68,69] and presence of multiple inhibitory receptors on T cells infiltrating PCNSL [70] might represent additional reasons why T cells unleashed upon PD-1 blockade did yield the expected benefit.…”
Section: Immune Checkpoint Blockers (Icbs)mentioning
confidence: 99%